Complicating Disorder: The Play of Interpretation and Resistance in Melanie Klein's Narrative of a Child Analysis - Clark, Hilary (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
This essay explores the challenge to the order/disorder binary offered by the dynamics of the psychoanalytic session, specifically one of Melanie Klein’s child analyses. It argues that the perception of psychoanalysis as normalizing is considerably complicated by the play of interpretation and resistance between analyst and child.